Odpowiedzi

Najlepsza Odpowiedź!
2009-10-05T19:56:58+02:00
(4 2/19 * 3⅙ - 5,2)/ (6+3¼ : 0,5)=(40/19*19/6-5,2)/(6+13/4*2) = (20/3-52/10)/(6+6½)=(20/3-26/5)/12½=(100/15-78/15)/(25/2) = 22/15*2/25=44/125
  • Użytkownik Zadane
2009-10-05T20:02:59+02:00
78/19*19/6-5,2 13-5.2 -4,2
----------------------= ----------= -------= -0,48
6+3 1/4:0,5 9 1/4:0,5 8,75
2009-10-05T20:13:02+02:00
(4 i 2/19 * 3 i 1/6 - 5,2)/ (6+3 i 1/4 : 0,5)=
=(78/19*19/6 - 5,2)/(6+13/4*2) =
=(13-5,2)/(6+6½)=
=(7,8)/12½=
=7,8 : 12,5=0,624